Pengembangan Ekstrak Etanol Buah Pepino (Solanum Muricatum Aiton) dalam Bentuk Granul Effervescent dengan Variasi Bahan Pengikat: Development of Pepino Fruit (Solanum muricatum Aiton) Ethanol Extract In The Form of Effervescent Granules with Various Binding Materials - Hamsinah, Hamsinah; Ririn, Ririn (Universitas Tadulako, 2020)
The aim of the investigation is to obtain a good preparations of effervescent granules of ethanol extract of pepino fruit (Solanum muricatum Aiton) based on parameter of flowability and repose angle, density, moisture content, loss on drying and dispersibility. Maceration method and ethanol 96% as the solvent is use to obtain the extract of pepino fruit (Solanum muricatum Aiton). There are three formula design of effervescent granules formula 1,2 and 3 each of which in variation of binder PVP K30 2%, 4% and 6% (w/w). The granules is obtain by wet granulation method in which ethanol extract of pepino fruit as the active ingredient. Results of evaluation showed that angle of repose range from 33.425-34.352o while flowability range from 5.84-6.66 g/second. Bulk density range from 0.519-0.570 g/ml, tap density 0.552-0.53 g/ml, true density 0.2005-1.22 g/ml. Uji porositas berkisar 6.36-44.609 % while the dispersibility range from 1.407-1.477 gram/second. Based on the results can be concluded that all granules possess good properties pharmaceutically.